Structural modelling of cause and effect factors of construction waste generation in Malaysian Construction Industry - Nagapan, Sasitharan (2014)
Construction industry contributes significantly in improving socio-economic development of a country. However, this industry faces serious problems of construction waste generated worldwide including Malaysia. Construction waste is results from various factors which are necessary to identify for reducing the waste generated in construction project. Hence, this study focused on developing a structural model of construction waste generation and determining the most important group that contributes to construction waste generation. The questionnaire consisted of 77 causative factors which then clustered into 7 groups and 13 effects factors of construction waste which are clustered into 3 groups. These factors and assigned groups were validated by 30 construction personnel (contractors, consultants and clients) during the pilot study. The actual survey was conducted with a total of 302 questionnaires were received by respond rate of 60%. The data analysis is carried out using SmartPLS software. A structural model of construction waste generation was developed based on 7 groups of causative factors and 3 groups of effect factors using Partial Least Squared-Structural Equation Modelling (PLS-SEM) technique. It was found that the model is fit due to the R² value of 0.451 (R2 ≥ 0.26 = substantial). The model identifies that all 10 groups are significant with t-value ≥ 2.58 from bootstrapping process of 5000 random samples. The model indicates that Handling of Materials and Equipment group has the highest impact on construction waste generation. Finally, this finding was validated by 22 construction practitioners who agreed that Handling of Material and Equipment group of factors contributes the highest amount of construction waste generation at site. This group of factors should be avoided during construction works to reduce the waste generation. The findings of this study are contributed to understand clearly the cause and effect factors of construction waste generation in Malaysia.